Apie prietarų dekonstrukciją supratime - Barkouski, Pavel (Problemos, 2004)
Due to program and therefore polemical, declarative and provocative character of this article it should be treated as a positive manifesto rather than piece of a scientific research. That allows it to restore for a while the concord on the level of language within the complicated mutual relations between philosophy and literature again. This situation also mediates the explicit absence of authoritative sources one should refer to, except for some explicative judgments of the acknowledged guru in the deconstruction business. What is yet an application area of the latter in a case of hermeneutical thinking? What can deconstruction of prejudices of comprehension as total hermeneutic care represent? What is left to do, when ritual has occupied the place of faith, and sacral words spoken thousand times threaten to interpret all properly and canonically if one does not doubt their magic power? It is just the crucial time for deconstruction, which one should see in the horizon of its three-dimensionality.
Keywords: deconstruction; comprehension; hermeneutics; critical theory; prejudices